(untitled) (World Bulletin of Public Health, 2025)
Intrauterine pathologies occupy one of the leading places in the structure of gynecological diseases, including the structure of female infertility. The widespread introduction of endovisual research methods, including hysteroscopy in gynecological practice has significantly expanded the possibilities of diagnosing and treating intrauterine pathologies. The high efficiency of this method is characterized by the possibility of simultaneous correction of the identified intrauterine pathology and restoration of reproductive function in women with uterine infertility. The article presents an analysis of the structure of intrauterine pathologies in women with infertility.